STABILISASI TANAH LIAT DENGAN KAPUR PADA KONSTRUKSI BADAN JALAN HUTAN DI PULAU LAUT - Rahardjo S Suparto; S Sutopo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
Subgrade construction is an important part in forest road building, Subgrade soils with a high clay content could not be used satisfactorily as forest road construction material unless it is treated to increase its stability. The improvement of the physical characteristics of clay soils related to subgrade construction can be achieved by mixing lime of certain proportion into the soil. The purpose of this investigation is to determine the amount of lime required for subgrade stabilization which have high clay content in Pulau Laut, South Kalimantan The investigation reveals the following :1. The efective amount of lime stabilization of soils is 7 percent of the dry weight of the soil, resulting in the following physical properties :- Bearing capacity is 167 kg/cm2 at air dry condition,- Percent of swell is 2.3,- Plasticity index is 25.5, and- pH is 9.00.2. Stabilization with 7 percent lime is most effective for use in forest road subgrade containing about 66% clay.